Penerapan NVDA berbasis metode SAS dalam meningkatkan kemampuan membaca permulaan Braille bagi anak tunanetra di SLB Negeri 01 Bantul - Djari, Tri Rizki Wahyu (Piramida Akademi, 2025)
The aim of this study is to determine the application of NVDA based on the SAS method in improving Braille initial reading ability for visually impaired children at SLB Negeri 01 Bantul. The problem is that there are two blind subjects who cannot read Braille fluently because they lack focus, lack motivation to learn, and have low fine motor skills. This study used a talking computer that has been installed with NVDA software and the SAS method. The application of NVDA software based on the SAS method aims to improve the ability to read Braille for visually impaired children. This study employed a quantitative approach with a pre-experiment method. The design of this study utilized one group pretest and posttest design. All of visually impaired students in grade 3 elementary school at SLB Negeri 01 Bantul were defined as the population. Data collection techniques were carried out using pretest and posttest. The data analysis in this study used descriptive statistical methods and non-parametric analysis techniques. To test the hypothesis, this study used the Wilcoxon test and for the normality test, used the kolmogorov smirnov test. Based on the results obtained, there is a difference between the sscores of the pretest and posttest results which is shown from the average score so that it can be concluded that there is an effect of the application of NVDA software based on the SAS method to improve the ability to read Braille for visually impaired children.